Studi Deskriptif tentang Pengambilan Keputusan pada Atlet Silat di Perguruan Tapak Suci Gorontalo - Trizki Diva Maharani; Umar Yusuf (UNISBA Press, 2024)
Abstract. In the world of sports, particularly in martial arts like pencak silat, decision-making is a critical aspect that can significantly affect an athlete's performance. Based on this phenomenon, the research problem formulated is: